Penguatan Keharmonisan Keluarga Muslim Melalui Taklim Parenting Islami Pada Program Gemar di Desa Bontokanang: Strengthening Muslim Family Harmony Through Islamic Parenting Lecture in the Gemar Program - Muhammad Nirwan Idris; Kurnaemi Anita (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This community service program aimed to strengthen Muslim families’ awareness of the importance of household harmony in nurturing a rabbani generation through an Islamic parenting lecture in the GEMAR program of IAI STIBA Makassar’s community service program in Bontokanang Village. GEMAR, or Gebyar Meriah Anak Ramadan, was implemented as a children’s religious development program through several Islamic competitions, including the call to prayer, young preacher performance, daily prayer memorization, short surah memorization, and Qur’anic recitation, followed by an Islamic parenting lecture for parents and the community. This program employed a descriptive-qualitative method with an educative-participatory approach. Data were obtained through activity observation, documentation, KKN implementation notes, participant responses, the village head’s testimony, and community appreciation. The findings indicate that GEMAR functioned not merely as a children’s festival but also as a family education medium connecting children’s religious development, parental roles, and community support. The Islamic parenting lecture strengthened participants’ understanding of the family as the first educational environment, parental role modelling, healthy communication, and the actualization of sakinah, mawaddah, and rahmah values in children’s education. The positive community response and the village head’s testimony indicate that the lecture theme was relevant to the needs of Muslim families. Program sustainability was pursued through the handover of guidance and management to the South Galesong DPC so that the activities could continue in a more organized manner.